2022
DOI: 10.1159/000524045
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Seizure Threshold and Other Behaviors in Adult Mice without Gross Neuroanatomic Injury after Late Gestation Transient Prenatal Hypoxia

Abstract: Intrauterine hypoxia is a common cause of brain injury in children resulting in a broad spectrum of long-term neurodevelopmental sequela, including life-long disabilities that can occur even in the absence of severe neuroanatomic damage. Postnatal hypoxia-ischemia rodent models are commonly used to understand the effects of ischemia and transient hypoxia on the developing brain. Postnatal models, however, have some limitations. First, they do not test the impact of placental pathologies on outcomes from hypoxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 92 publications
(171 reference statements)
1
6
1
Order By: Relevance
“…Our data, obtained using the OF test, revealed that exposure to prenatal inflammation caused increased anxiety in LPS-exposed mature (P68), but not pre-adolescent (P27), male pups, while female pups from both age groups remained unaffected. An increase in anxiety levels in LPS-exposed male pups detected in our study is consistent with previously published data which were obtained using both systemic immune activation [51-59], intrauterine exposure to infectious agents or their ligands [21, 60], and prenatal hypoxia [35]. For instance, using the OF test, Dada and co-authors showed that mouse offspring that received intrauterine LPS injections at E17 had elevated anxiety levels at P60, although a sex-specific effects were not tested [60].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data, obtained using the OF test, revealed that exposure to prenatal inflammation caused increased anxiety in LPS-exposed mature (P68), but not pre-adolescent (P27), male pups, while female pups from both age groups remained unaffected. An increase in anxiety levels in LPS-exposed male pups detected in our study is consistent with previously published data which were obtained using both systemic immune activation [51-59], intrauterine exposure to infectious agents or their ligands [21, 60], and prenatal hypoxia [35]. For instance, using the OF test, Dada and co-authors showed that mouse offspring that received intrauterine LPS injections at E17 had elevated anxiety levels at P60, although a sex-specific effects were not tested [60].…”
Section: Discussionsupporting
confidence: 93%
“…Statistics were performed as described previously using R-studio [35]. Briefly, we used mixed models with generalized estimating equations in the geepack package in R with cohort as the random effect [36].…”
Section: Methodsmentioning
confidence: 99%
“…However, there were differences between these prior studies and our current study, in which sustained hypoxia impaired cognitive function in young adult female offspring [114], decreased repetitive behaviors in young adult male offspring [76,111], and increased anxiety-like behaviors in young adult male offspring [76,111], indicating that the type of hypoxic exposure during this critical period of brain development is important.…”
Section: Discussioncontrasting
confidence: 85%
“…have found equivocal ndings that range from social impairments in male offspring with no effects in female offspring [109,110] to social impairments in female offspring with no effects in male offspring [76,111] or social impairments in both sexes [112]. Reports of sex differences in cognition due to gestational hypoxia have been observed, with impairment observed in male offspring [109,113], female offspring [114], or neither sex [76,112,115].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation